Effects of Interplanting Medicinal Herbs on Runoff, Sediment and Nitrogen and Phosphorus Losses in Young Oil Tea Plantation on Red Soil Sloping Field - YAN Shijie; DUAN Jian; SHEN Faxing; XIE Dongjie; ZHENG Haijin (Shuitu Baochi Xuebao)
[Objective] To investigate the effects and applicability of different intercropping patterns of medicinal herbs on water, soil, and nutrient losses in young oil tea gardens on red soil slopes. [Methods] Runoff plot experiments were carried out in Jiangxi Province, a major province for cultivating traditional Chinese medicinal herbs, with interplanting above-ground harvested medicinal herb of Ai pattern (YA), interplanting below-ground harvested medicinal herb of Yujin + vegetative hedges pattern (YY), traditional conservation measure of straw mulching + moisture furrow pattern (YC), and clean tillage pattern for control (CK). Observation of runoff, sediment, nitrogen and phosphorus losses under natural rainfall events, and comprehensive benefit evaluation of each pattern were carried out. [Results] (1) All conservation measures significantly reduced water, soil, and nutrient losses in young oil tea plantations, except for the clean-tillage mode. Compared with CK, the runoff reduction effects of YA, YC and YY amounted to 15.22%, 67.30% and 64.12%, respectively; the sediment reduction effects amounted to 72.63%, 97.19% and 98.19%, respectively; the decrease in total nitrogen (TN) loss was 57.86%, 96.53% and 95.87%, respectively; and the decrease in total phosphorus (TP) loss was 32.18%, 98.62% and 98.86%, respectively. (2) Under moderate rain, heavy rain and rainstorm, YY pattern all showed good soil and water conservation and nutrient interception effects, with runoff reduction effects and sediment reduction effects ranged from 45.11% to 83.25% and 96.08% to 99.02%, respectively. The nitrogen and phosphorus reduction effects ranged from 83.02% to 99.14% and 88.38% to 99.65%, respectively; whereas YA pattern only had a better nutrient interception effect under moderate and heavy rain, the soil and water conservation effect under heavy rain was not obvious. (3) Based on the TOPSIS model, the comprehensive benefits of the four patterns were evaluated and ranked as YY (0.48) > YC (0.29) > YA (0.23) > CK (0.02). [Conclusion] Below-ground harvesting of medicinal herb Yujin + plant hedge mode is the most economical and effective management measure to control soil erosion and nutrient losses of young oil tea plantation on red soil slope in this experiment. Selecting medicinal herbs with staggered harvesting period and erosion risk period will better utilize the ecological benefits of interplanting medicinal herbs, and can avoid additional nutrient losses of young oil tea plantations.